Unilateral and bilateral radioactive stent insertion in patients diagnosed with inoperable hilar cholangiocarcinoma: a comparative analysis - Jin, Jin-Long; Li, Wei; Wu, Zhi-Xian (Frontiers in Oncology, 2024)
BackgroundWhile hilar cholangiocarcinoma (HCCA) patients commonly undergo radioactive stent (RS) insertion treatment, the relative benefits of unilateral versus bilateral RS insertion procedures remain to be established. Accordingly, this study was designed to evaluate the relative safety and efficacy of percutaneous bilateral and unilateral RS insertion for patients with HCCA.MethodsIn total, 126 HCCA patients who underwent unilateral (n=64) or bilateral (n=62) RS insertion from January 2017 - December 2021 were included in this analysis. Treatment efficacy and long-term outcomes were compared between groups. The primary endpoint was stent patency, and the secondary endpoints included technical success rate, clinical success rate, local control rate, overall survival (OS), and complications.ResultsThe respective technical success rates in the unilateral and bilateral groups were 90.6% (58/64) and 93.5% (58/62) (P = 0.782). The clinical success rates were 82.8% and 86.2% in unilateral and bilateral groups, respectively (P = 0.608). Both groups exhibited comparable medial post-intervention bilirubin levels (100 vs. 99 μmol/L; P = 0.501), and restenosis occurred in 12 (20.7%) and 15 (25.9%) patients over the follow-up interval (P = 0.510). The stent reintervention rate was significantly higher in the unilateral group than bilateral group (66.7% vs. 0.0%, P < 0.001). The median stent patency in the unilateral and bilateral groups was 189 and 210 days, respectively (P = 0.796), while the median OS interval was 222 and 229 days, respectively (P = 0.969). Comparable cholangitis (17.2% vs. 22.4%, P = 0.485) and cholecystitis (3.4% vs. 3.4%, P = 1.000) rates were also detected in these two groups.ConclusionsIn summary, HCCA patients exhibit comparable efficacy when undergoing unilateral and bilateral radioactive stenting, suggesting that unilateral RS can be routinely performed owing to the simpler nature of this procedure.